The Effectiveness and Durability of Organic Olive Oil, Bengkoang, and Butterfly Pea Flower Soap for Dry Skin - R. A Mukti; F. H Fatmasari; I Nuraini; U. M. Rochmawati; K. A. Trisna Dewi (Jurnal Penelitian Pendidikan IPA, 2025)
The skin is the outermost part of the body, which is exposed to all types of pollutants from the air, including microbes. Therefore, it requires an effective cleanser to protect it. However, the cleanser must also be able to maintain skin moisture. The selection of ingredients used for soap is olive oil, jicama, and butterfly pea flowers. These ingredients contain oleic acid, vitamin C, and flavonoids, which are effective in moisturizing, antibacterial, and antioxidants. The purpose of this study was to determine the effectiveness of soap for cleaning, protecting, and moisturizing, to determine the durability by examining the soap's pH, and its antibacterial effectiveness. The methodology used was an experimental design with a one-group pretest and posttest design, which was analyzed quantitatively descriptively. Data collection used experiments, questionnaires, and observation sheets. Observations were in the form of measuring moisture levels using a digital skin analyzer. The results of the T test (paired sample t-test) were t = 11.625, while the T table was 2.04 with a Sig = 0.000 < 0.05 (2 tails). Then the calculated T > T table, so H1 was accepted. The conclusion is that there is an effect of using organic soap from olive oil, bengkoang, and butterfly pea flowers, with good durability and a stable pH, while microbiological tests on Escherichia coli bacteria were not as good as eco enzyme soap.